Anaesthetic Management of Parturient with Acute Atrial Fibrillation for Emergency Caesarean Section - Madhu Gupta; Shalini Subramanian; Preeti Adlakha (Case Reports in Anesthesiology)
A 31-year-antenatal lady with critical mitral stenosis presented for emergency caesarean section with fetal distress. She had acute onset atrial fibrillation. She was given a combined spinal epidural (CSE) anaesthesia and her arrhythmia was successfully managed after delivery of the baby with intravenous calcium channel blocker. Mitral stenosis is the most common valvular heart disease complicating pregnancy in developing countries. The physiological changes during pregnancy may exacerbate their cardiac symptoms. They may present with complications like congestive cardiac failure, atrial fibrillation, or pulmonary thromboembolism during the antenatal, intrapartum, or postpartum period. Here we discuss the management of parturient woman with high maternal and fetal risk presenting for emergency caesarean. The merits of regional anaesthesia and the importance of invasive monitoring are also discussed.